Planar air-bearing microgravity simulators: Review of applications, existing solutions and design parameters. (March 2016) - Rybus, Tomasz; Seweryn, Karol
Abstract: All devices designed to be used in space must be thoroughly tested in relevant conditions. For several classes of devices the reduced gravity conditions are the key factor. In early stages of development and later due to financial reasons, the tests need to be done on Earth. However, in Earth conditions it is impossible to obtain a different gravity field independent on all linear and rotational spatial coordinates. Therefore, various test-bed systems are used, with their design driven by the device׳s specific needs. One of such test-beds are planar air-bearing microgravity simulators. In such an approach, the tested objects (e.g., manipulators intended for on-orbit operations or vehicles simulating satellites in a close formation flight) are mounted on planar air-bearings that allow almost frictionless motion on a flat surface, thus simulating microgravity conditions in two dimensions. In this paper we present a comprehensive review of research activities related to planar air-bearing microgravity simulators, demonstrating achievements of the most active research groups and describing newest trends and ideas, such as tests of landing gears for low-g bodies. Major design parameters of air-bearing test-beds are also reviewed and a list of notable existing test-beds is presented. Highlights: Planar air-bearing test-beds are one of possible solutions to simulate microgravity. We present a review of research activities related to planar air-bearing simulators. Design parameters are reviewed and list of existing test-beds is presented. Applications of air-bearing test-beds include: formation flying, manipulator control. New interesting applications: experiments with landing gears for low-g bodies.